Kangnam mong : Hwang Sŏg-yŏng changp'yŏn sosŏl - Hwang, Sŏg-yŏng, 1943- (Kyŏnggi-do P'aju-si : Ch'angbi, 2012)
Epic novel covering the South Korea's history of modernization with capitalism in 20th century. Describes panoramic lives of five people who have built their golden cows in Kangnam and their shattered dreams with the collapse of Sampung Department store in 1995.
"Hwang Sŏg-yŏng munhak 50-yŏn t'ŭkpyŏl hanjŏngp'an"--Case.
Keywords: Samp'ung Paekhwajŏm (Seoul, Korea) -- Fiction; Building failures -- Korea (South) -- Seoul -- Fiction; Korea (South) -- History -- 20th century -- Fiction; Kangnam (Seoul, Korea) -- History -- 20th century -- Fiction